Kajian Tipologi Perabot pada Restoran Padang di Surabaya - Lintu, Caroline (Intra, 2015)
Padang cuisine is one of the various Indonesian famous foods that is loved by many locals and also tourists. Padang restaurants have an unique characteristics in their serving method which is every menu dishes available are served onto the table, where waiters put dozens of plates directly to the guests table. Aside from the serving method, Padang restaurants always have a display window of cuisine beside the main entrance which makes people easily recognizes a Padang restaurant. Activities inside the restaurant are never far from the furniture, which is why the unique serving system is closely related to furniture. The high numbers of Padang restaurants in Surabaya makes researchers interested in doing a typology research of its furniture. Furniture of Padang restaurant in Surabaya differ and each have their own unique characters. Furniture are not just being studied from the shape and size aspects only, but also from the furniture arrangement, as the position of furniture affects the activities inside the restaurant. By studying this matter by typology, the different of one restaurant with another can be compared so an affinity and similarity can be concluded for one to another. The result of analysis will show a similarity and differences in arrangement, dimension, and shape of furniture from each Padang restaurants. This difference and similarity analysis that is resulted from those groupings will be a conclusion about typology of Padang restaurants in Surabaya.